ASPECTS FOR INCREASING THE EFFECTIVENESS OF THERMO COMPRESSOR MULTI EFFECT DISTILLATION PLANTS - Alrobaei, Hussain (Nahrain University College of Engineering Journal, 2008)
Currently, there is a strong demand for efficient seawater desalination plants, which can meet the tougherenvironment regulation and energy saving requirements. From this standpoint the present work was undertakento include the proposed schemes for repowering and modification of grid connected Thermo-Compressor MultiEffect Distillation (TC-MED) plants. The Modified Solar Distillation Plant (MSDP) during sunny periods maybe applied to full cogeneration mode of operation with feeding the surplus electricity into Electrical Power Grid(EPG). To investigate the potential effect of the proposed schemes a computational models have been developedand implemented on simulation programs. The study result shows the effectiveness of proposed schemes. For thecase study (MSDP with Low backpressure Turbine (LT) and annual share of solar thermal power generation 22.5%) the economical effect amounts 216.8 ton/year for each MW design thermal power consumption of TC-MEDand the corresponding decrease in MSDP exhaust gases emission (carbon dioxides (CO2) 660 ton/year.MW ,nitrogen oxides (NOx) 286.3 kg/year.MW). Moreover implementation of MSDP-LT scheme for repowering andmodification of conventional six effects TC-MED plant will increase the above sited environmental and thermaleffectiveness by 72.5 % due to the 24989.8 ton/year.MW of annual solar distilled water production besidesboosting 723.9MW.hr/year.MW of solar electricity in EPG.